EVOLUTION OF AGRIBUSINESS AND ITS CHALLENGES IN BRAZIL (CIPEEX, 2024)
BRAZIL IS ONE OF THE LARGEST AGRICULTURAL PRODUCERS IN THE WORLD, WHICH MEANS THAT CHALLENGES IN THIS SECTOR ARE CONSTANT. IN THIS WAY, UNDERSTANDING THE ADVANCES AND CHARACTERISTICS OF THIS SECTOR IS IMPORTANT SO THAT DECISIONS CAN BE MADE BASED ON IN FACTS SEEKING SOLID AND SUSTAINABLE GROWTH IN AGRICULTURE. IN THIS REGARD, THIS WORK AIMED TO UNDERSTAND THE MAIN ASPECTS THAT LED TO THE AGRIBUSINESS IN BRAZIL TO BE A NATIONAL HIGHLIGHT, POINTING OUT LEGAL ISSUES, AS WELL AS ENVIRONMENTAL ISSUES THAT PROMOTED THE DEVELOPMENT OF THIS SECTOR. A METHODOLOGY USED IN THIS STUDY, IT IS A LITERATURE REVIEW BASED ON SCIENTIFIC DOCUMENTS PUBLISHED IN ACADEMIC JOURNALS AND IN INSTITUTIONAL BODIES, WITH THE AIM OF RESPONDING TO THE FOLLOWING PROBLEM, WHICH FACTORS INFLUENCED THE DEVELOPMENT OF AGRIBUSINESS IN BRAZIL? IT WAS OBSERVED THAT BRAZIL IS ONE OF THE BIGGEST NAMES IN THE GLOBAL AGRICULTURAL MARKET. ITS EXTENSIVE CULTIVATION AREA ALLOWS BRAZIL TO STAND OUT AND OBTAIN IMPORTANT RESULTS, SO THAT THIS SECTOR REPRESENTS A SIGNIFICANT PORTION OF GDP. SO THAT THIS AREA DEVELOPED AND DEVELOPED EVEN FURTHER, BODIES LIKE EMBRAPA PROVIDE ASSISTANCE IN RESEARCH THAT BOOSTS GROWTH. HOWEVER, ONE OF THE BIG CHALLENGES LIES IN ASSOCIATING THE SECTOR'S GROWTH IN A SUSTAINABLE WAY, AVOIDING DEFORESTATION AND GREENHOUSE GASES STUDY, BEING A STRONG FIELD OF RESEARCH. IN GENERAL, BRAZIL PRESENTS A GROWING MARKET VALUE IN THE AGROINDUSTRY, THAT NEEDS TO BE ASSOCIATED WITH SUSTAINABLE DEVELOPMENT IN ORDER TO REMAIN AMONG THE GLOBAL PROTAGONISTS IN AGRICULTURAL PRODUCTION.
Keywords: Agroindustry; Agricultural production; Sustainability.